The comparison between modified kligman formulation versus kligman formulation and intense pulsed light in the treatment of the post-burn hyperpigmentation - Siadat, Amir Hossein (Adv Biomed Res, 2016)
BACKGROUND: Post inflammatory hyperpigmentation (PIH) is a common problem occurs following many dermatologic diseases and medical interventions. Different modalities including topical agents, lasers and intense pulsed light (IPL) are suggested for treatment of the post-burn PIH. In the current study, we evaluated the efficacy of IPL plus modified Kligman cream (MODIFIED KLIGMAN CREAM) versus MODIFIED KLIGMAN CREAM alone in the treatment of the post-burn PIH. MATERIALS AND METHODS: This was a randomized, non-blinded clinical trial. A total of 53 patches of post-burn PIP in 14 patients were randomized to receive either two sessions of IPL plus modified Kligman formula or kligman formula for 2 months. The patients were recommended to apply MODIFIED KLIGMAN CREAM cream for 12 h at night. RESULTS: According to our results, the patients in the MODIFIED KLIGMAN CREAM + IPL group had higher satisfaction as compared with MODIFIED KLIGMAN CREAM alone (P = 0.000) (Mann–Whitney test). In addition, according to physician evaluation, the patients in the MODIFIED KLIGMAN CREAM + IPL group had higher satisfaction as compared with MODIFIED KLIGMAN CREAM alone (P = 0.000) (Mann–Whitney test). No side effects except a little irritation, erythema and exfoliation due to MODIFIED KLIGMAN CREAM cream were seen in the patients. CONCLUSIONS: The results of our study showed the better efficacy and faster response of the IPL plus modified Kligman formula versus modified Kligman formula in the treatment of the post-burn PIH. To better determine the efficacy of IPL in treatment of the post-burn PIP, more extensive studies as randomized, double-blinded clinical trial are recommended.